Initial Outcomes of Cyanoacrylate Closure, VenaSeal System, for the Treatment of the Incompetent Great and Small Saphenous Veins. (November 2017) - Park, Insoo
Purpose: Cyanoacrylate closure of the saphenous vein with the VenaSeal system is a new technique just approved on December 2016 in Korea. Therefore, there are seldom reports about postprocedural outcomes of VenaSeal system in Asian countries. We report the initial outcomes of VenaSeal system for the treatment of great saphenous veins (GSVs) and small saphenous veins (SSVs) as a first report in Korea. Methods: Thirty-four patients with incompetent saphenous veins (47 GSVs and 16 SSVs) were treated at a single session. Concomitant phlebectomy was performed in 15 (44.1%) of 34 patients. All procedures were started with local anesthesia with music therapy and switched to intravenous sedation if patient requested. Patients revisited the clinic on 10 days, 1 month, and 3 months after surgery. Postprocedural evaluations including numerical pain rating score, revised Venous Clinical Severity Scores (rVCSS), and Aberdeen Varicose Vein Questionnaires were checked. Duplex ultrasound was performed on 10 days, 1 month, and 3 months. Results: All treated veins (47 GSVs and 16 SSVs; 100%) had complete closure by duplex ultrasound during the follow-up period. Mean numerical pain rating scale of 6 hours after procedure was 2.7. The rVCSS was improved during the follow-up period. Phlebitis-like "abnormal skin reaction" in the treatment area was occurred in 8 (23.5%) of 34 patients and recovered fully in 2 weeks. Conclusions: Cyanoacrylate closure, VenaSeal system, is safe and effective for the treatment of incompetent saphenous veins.